International economic papers - International economic association; International Economic Association (New York : Macmillan and Co., 1956)
The present volume starts with a learned investigation into the history of Say's Law, a subject which has recently been re-examined by a number of writers on monetary theory, following Lange's article of 1942.
Volume 6.
Includes bibliographical footnotes
hza 28/01/2019
Loans
Keywords: Economics